Pengaruh Permainan Memancing Angka terhadap Kemampuan Konsep Bilangan Anak Usia 5-6 Tahun Di TK Pertiwi Kecamatan Bone Kabupaten Bone Bolango - Hajira Burui; Setiyo Utoyo; Icam Sutisna (Student Journal of Early Childhood Education, 2022)
The purpose of this study was to find out the influence of number fishing games on the ability of the concept of numbers of children aged 5-6 years. This study is a quantitative study with experimental methods and using test performance data collection techniques, the subjects of this study are 22 students. Data analysis consists of two parts, descriptive and quantitative used in comparing the test value of the initial condition (pre-test) and the final condition (post-test). The results showed that: before the use of game media tends to be high who cannot know the concept of numbers, compared to the use of children’s game media can know the concept of numbers.